Interior of Red Brick Dorm (1965)
Two men are in a red brick dorm. There is a certificate on the desk for Richard Donald [Gratchen?] from the California Delta Chapter of the Alpha Zeta fraternity. There is a badge on the bulletin board from the Susanville Police.